Screening and the epidemic of thyroid cancer in China: An analysis of national representative inpatient and commercial insurance databases. Issue 5 (28th September 2020) - Liu, Yihao; Lai, Fenghua; Long, Jianyan; Peng, Sui; Wang, Haibo; Zhou, Qian; Li, Bin; Su, Lei; Gan, Lanxia; Shi, Ying; Lv, Weiming; Li, Yanbing; et al.
Abstract: Reasons behind the rapid increase of thyroid cancer (TC) in China are uncertain. We assessed the burden of TC and the role of access to screening and salt iodization. We analyzed two national databases in China: Hospital Quality Monitoring System (HQMS) and China Reinsurance Company (CRC) database. HQMS covered 1037 (44.3%) Class 3 hospitals and 76 263 617 Class 3 hospital inpatients in 2013 to 2017 and CRC covered 93 123 018 clients in 2000 to 2016. The proportion of TC inpatients among inpatients in HQMS and TC incidence in critical illness insurance buyers were used to evaluate the association with screening and iodine status. Between 2013 and 2017, the proportion of TC patients in HQMS with urban employee medical insurance and good access to screening increased sharply while there was little change among those with the other two forms of medical insurance. Across provinces, the proportion of TC inpatients in HQMS was positively correlated with per capita disposable income but not with median urinary iodine. Similar findings were observed in the CRC database. In 2017, approximately 1000 individuals were overdiagnosed with TC daily. We conservatively forecast that 5.1 million healthy individuals would become TC patients unnecessarily between 2019 and 2030. Our findings suggested the epidemic of TC in China was substantially underestimated. It was associated with screening but not with salt iodization. Abstract : What's new? In recent decades, the incidence of thyroid cancer has increased rapidly worldwide. In China, the role of thyroid cancer screening as part of regular health checks and potential overdiagnosis remain unclear. Moreover, there are concerns among the general public that mandatory salt iodization may have contributed to the epidemic of thyroid cancer. Here, the authors found that the increase in thyroid cancer in China is associated with increased access to health care and screening, but not with salt iodization. Moreover, the results suggest that approximately 1000 individuals are overdiagnosed with thyroid cancer daily, calling for urgent measures to prevent overdiagnosis.